The use of cold porcelain orthoses to implement the act of playing of a child with motor deficit - Marilda Ferraz Santana; Ana Paula Morais Braga (Revista Brasileira em Promoção da Saúde, 2012)
playing of the child with motor deficit. Methods: Applied research, quantitative and qualitative, in the Center for Integrated Healthcare (NAMI) in Fortaleza - CE, Brazil. The investigation occurred in the period from February to June 2008. Sample of 22 children, 14 selected in the survey entitled “Reduction in costs for making orthoses” and 8 indicated by professionals. We applied semi-structured interviews with officials, evaluate the play behavior based on the Protocol of Ferland. In the analysis of qualitative information, we used Bardin’s Content Analysis. For quantitative data, we used the statistical treatment of Morettin. Results: The qualitative categories were organized into three: the parents’ opinion about the act of playing of their children, type of toy and improvement in occupationalperformance with the use of orthosis. The quantitative analysis allowed the consolidation of data in tables, after the Behavior Assessment Playful, applied in the beginning and in the end of the study. Conclusions: This study showed, therefore, that the use of “cold porcelain” orthoses interfered, overwhelmingly, both in performing of the act of playing of the children who participated in this research, as well as in occupational performance in various areas, passing by significant changes, bringing value also in the interest, ability to perform an activity and relationships and feelings.